A Modeling Workbench for the Development of Situation-specific Test Co-Migration Methods - Jovanovikj, Ivan; Thottam, Anu Tony; Joseph Vincent, Vishal; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 9th International Conference on Model-Driven Engineering and Software Development)

Simplifying Robot Programming using Augmented Reality and End-User Development - Yigitbas, Enes; Jovanovikj, Ivan; Engels, Gregor (Proceedings of the 18th IFIP TC13 International Conference on Human-Computer Interaction (INTERACT 2021))

Augmented and Virtual Reality Object Repository for Rapid Prototyping - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 8th International Working Conference on Human-Centered Software Engineering (HCSE'20))

A Model-Driven Mutation Framework for Validation of Test Case Migration - Jovanovikj, Ivan; Weidmann, Nils; Yigitbas, Enes; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the First International Conference on Systems Modelling and Management, ICSMM 2020)

VR Training for Warehouse Management - Yigitbas, Enes; Jovanovikj, Ivan; Scholand, Janis; Engels, Gregor (Proceedings of the 26th ACM Symposium on Virtual Reality Software and Technology (VRST))

Challenges in Model-Driven Development of Multi-Platform Augmented Reality Applications - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 22st Workshop Software-Reengineering & Evolution (WSRE) & 11h Workshop Design for Future (DFF))

Concept-based Co-Migration of Test Cases - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 8th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD)

Test Case Co-Migration Method Patterns - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Software Engineering 2020 Workshopband)

On the Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Handling Security, Usability, User Experience and Reliability in User-Centered Development Processes - IFIP WG 13.2/13.5)

Validating Test Case Migration via Mutation Analysis - Jovanovikj, Ivan; Nagaraj, Achyuth; Yigitbas, Enes; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the 1st IEEE/ACM International Conference on Automation of Software Test AST)

Development Framework for Context-Aware Augmented Reality Applications - Krings, Sarah Claudia; Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Proceedings of the 12th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2020))

Integrated Model-driven Development of Self-adaptive User Interfaces - Yigitbas, Enes; Jovanovikj, Ivan; Biermeier, Kai; Sauer, Stefan; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))

Component-Based Development of Adaptive User Interfaces - Yigitbas, Enes; Josifovska, Klementina; Jovanovikj, Ivan; Kalinci, Ferhat; Anjorin, Anthony; Engels, Gregor (Proceedings of the 11th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2019))

Detection and Resolution of Data-Flow Differences in Business Process Models - Jovanovikj, Ivan; Yigitbas, Enes; Gerth, Christian; Sauer, Stefan; Engels, Gregor (Information Systems Engineering in Responsible Information Systems - CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings)

Modular Construction of Context-Specific Test Case Migration Methods - Jovanovikj, Ivan; Yigitbas, Enes; Grieger, Marvin; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

Towards Model-based Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 21st Workshop Software-Reengineering & Evolution (WSRE) & 10th Workshop Design for Future (DFF))

On-the-fly Usability Evaluation of Mobile Adaptive UIs through Instant User Feedback - Yigitbas, Enes; Jovanovikj, Ivan; Josifovska, Klementina; Sauer, Stefan; Engels, Gregor (Proceedings of the 17th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT 2019))

A Model-based Framework for Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Handling Security, Usability, User Experience and Reliability in User-Centered Development Processes (IFIP WG 13.2 & WG 13.5 International Workshop @ INTERACT2019))

Poster: CrossEcore: An Extendible Framework to Use Ecore and OCL across Platforms - Schwichtenberg, Simon; Jovanovikj, Ivan; Gerth, Christian; Engels, Gregor (Proceedings of the 40th International Conference on Software Engineering, ICSE 2018 - Companion Volume)
Today, model-driven approaches are a cornerstone in modern software development. The Eclipse Modeling Framework (EMF) is highly adopted in practice and generates Java code from platform-independent models with embedded Object Constraint Language (OCL) expressions. However, applications that target multiple platforms like Android, iOS, Windows, web browsers usually need to be implemented in different programming languages. Feature-complete Ecore and OCL runtime APIs are not available for all these platforms, such that their functionality has to be re-implemented. In this paper, we present CrossEcore: A multi-platform enabled modeling framework that generates C#, Swift, TypeScript, and JavaScript code from Ecore models with embedded OCL. An OCL compiler translates OCL expressions into expressions of the target language. The Ecore and OCL API can be consistently used across platforms, which facilitates application portability. CrossEcore is also extendible and can be easily adopted for new programming languages.

Test Case Migration: A Reference Process Model and its Instantiation in an Industrial Context - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan (Joint Proceedings of the Workshops at Modellierung 2018 co-located with Modellierung 2018, Braunschweig, Germany, February 21, 2018.)